The role of islamic lifestyle and healthy nutrition in accordance with the recommendations of islam and the holly quran by focusing on the risk of cancer incident - Jabbaripour, Pooneh; Somi, Mohammad Hossein; Roshani, Ali; Dolatkhah, Roya (Journal of Community Medicine and Health Solutions, 2020)
Background: The Islamic religion has emphasized the importance of health and well-being, and Muslims have recognized the value of a good and healthy life based on Islamic recommendations. Health-oriented lifestyle is a multi-dimensional phenomenon that is the purpose of this study to investigate the Islamic lifestyle. Methods: In this review study, we tried to explore practical strategies in Islam through access to credible sources in the form of a descriptive article on achieving a healthy lifestyle in nutrition. For this purpose, using keywords and electronic and manual searches in authentic Islamic and medical sources, information was searched and collected to answer the research question. Results: Based on the results of the reviewed studies, the guidelines of Islamic religion and beliefs are mainly based on improving lifestyle factors and dietary habits. It has been emphasized that adherence to the Islamic dietary guidelines and lifestyle, may lead to less risk of diseases. Conclusion: Given the availability of valuable nutritional resources and instructions in Islam to prevent and combat nutrition-related diseases, these theories can be applied and prevent from spreading and creating malnutrition-related diseases; the guidelines of Islam on healthy lifestyles in nutrition can be recommended to the world as a basic strategy.